Evaluation of Growth Patterns and Body Composition in C57Bl/6J Mice Using Dual Energy X-Ray Absorptiometry. (10th July 2014) - Gargiulo, Sara; Gramanzini, Matteo; Megna, Rosario; Greco, Adelaide; Albanese, Sandra; Manfredi, Claudio; Brunetti, Arturo
Abstract : The normal growth pattern of female C57BL/6J mice, from 5 to 30 weeks of age, has been investigated in a longitudinal study. Weight, body surface area (BS), and body mass index (BMI) were evaluated in forty mice. Lean mass and fat mass, bone mineral content (BMC), and bone mineral density (BMD) were monitored by dual energy X-ray absorptiometry (DEXA). Weight and BS increased linearly (16.15 ± 0.64 – 27.64 ± 1.42  g; 51.13 ± 0.74 – 79.57 ± 2.15  cm 2, P < 0.01 ), more markedly from 5 to 9 weeks of age ( P < 0.001 ) . BMD showed a peak at 17 weeks (0.0548 ± 0.0011  g/cm 2 * m, P < 0.01 ). Lean mass showed an evident gain at 9 (15.8 ± 0.8  g, P < 0.001 ) and 25 weeks (20.5 ± 0.3  g, P < 0.01 ), like fat mass from 13 to 17 weeks (2.0 ± 0.4 – 3.6 ± 0.7  g, P < 0.01 ). BMI and lean mass index (LMI) reached the highest value at 21 weeks (3.57 ± 0.02 – 0.284 ± 0.010  g/cm 2, resp.), like fat mass index (FMI) at 17 weeks (0.057 ± 0.009  g/cm 2 ) (P < 0.01 ). BMI, weight, and BS showed a moderate positive correlation (0.45–0.85) with lean mass from 5 to 21 weeks. Mixed linear models provided a good prediction for lean mass, fat mass, and BMD. This study may represent a baseline reference for a future comparison of wild-type C57BL/6J mice with models of altered growth.